EVALUASI PROGRAM PENANGGULANGAN HIV DAN AIDS (Studi pada Layanan Konseling dan Tes HIV dalam Penanggulangan HIV dan AIDS di Kecamatan Semarang Utara) - Putri Uswatul Khasanah; Ari Subowo (Journal of Public Policy and Management Review, 2018)
The health issue currently faced by Indonesia is the high of HIV and AIDS numbers. North Semarang Sub-District is the region that has the highest numbers of HIV case. Counseling service and HIV test have been conducted in North Semarang since 2013 through Bandarharjo and Bulu Lor Puskesmas. However, the numbers of HIV cases are still high. The research aimed to describe and analyze the implementation of counseling service and HIV test in preventing HIV and AIDS in North Semarang Sub-District and describing the factors related to the cases. This research used descriptive qualitative. The result of the research showed that the implementation of counseling service and HIV test in North Semarang had been effective that was seen by the upright of HIV diagnosis. People also obtained HIV treatment service and the knowledge of people about HIV increased. The equity had been achieved. It could be seen that people obtained the benefits of the service, fund distribution and the program had been fit with society’s condition. However, the responsiveness of society had not been achieved. People had followed the counseling routinely. They were comfortable with the program result but the participation was only dominated by pregnant women. Encourage factors in counseling service and HIV test in North Semarang were the support of counselor, the availability of treatment service, mobile counseling and affordable cost. Whereas, the obstacle factors were, the difficulty in obtaining patients’ information, there was side effect of ARV, the lack of people’s participation and archiving the data. The suggestion that can be given are, increasing people’s knowledge, increasing the knowledge of counselor, family support, increasing creativity in socialization and improving archiving the data.